Pelatihan Membuat Kerajinan Tangan Aksesoris Dari Manik-Manik Untuk Meningkatkan Inovasi-Creativepreneurship Pada Masyarakat - Rendy Prayogi; Mhd. Rusdi Tanjung; Fhery Agustin; Dila Viona Salsabila (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2025)
Handicrafts have become an integral part of Indonesian society as a form of livelihood that also has artistic value with selling prices that vary depending on the level of difficulty. There are many types of handicrafts, such as those made from woven bamboo, ceramics, used materials, beads and leather. The development of fashion in the current era is very rapid. One of them is beads. Beads are small decorative objects that have various profitable business opportunities. The discovery of beads was part of the Indonesian cultural revolution because of their important function and quality so they are still produced and used from the past until now. The aim of this service is to improve the quality of human resources and increase the existence of MSMEs through bead craft training, namely making cellphone straps, bracelets and key chains. The methods used are coordination, training, mentoring, follow-up planning and reflection. The process of implementing this work program is gradual, continuous and ongoing. The results of the bead craft training activities had a positive impact in that all residents who regularly took part in the training succeeded in practicing it independently, so that creativity and innovation in producing contemporary products could be realized. The results of the interviews at the reflection stage showed that all participants who initially could not make bead crafts, after going through training were 100% able to make the bead products they were interested in. So this bead craft training is highly recommended as an increase in creativity.